PENGARUH MODEL PROBLEM BASED LEARNING (PBL) TERHADAP LITERASISAINTIFIK SISWA KELAS 3 SD - Dinda Resty Indrawan; Din Azwar Uswatun; Dyah Lyesmaya; Herman Herdiana; Bangbang Ilhami (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article explains the influence of the Problem-based Learning (PBL) model on the scientific literacy of third-grade students in elementary school. The research method used was a quasiexperimental design with a non-equivalent control group. The respondents of the study involved one teacher and 18 students. Data on students' scientific literacy abilities were obtained from the pretest and posttest, then analyzed by using SPSS 26.0 for the Windows version. After utilizing normality and homogeneity tests, the control and experimental classes were determined to have a regular and homogenous distribution. The hypothesis was tested by using the Independent Sample t-test in the study. The findings indicated a significance value of 0.000 < 0.05, which indicates that H0 was rejected and H1 was accepted. It could be described that there was a statistically significant difference in values between the experimental class that utilized the PBL model and the control class that did not use the PBL model. According to the data analysis, the PBL model has an influence on third-grade elementary school students' scientific literacy in the domain of competence or scientific processes. Thus, the authors recommended that teachers may include the PBL model in their classroom instruction.